2021
DOI: 10.1093/mnras/stab2849
|View full text |Cite
|
Sign up to set email alerts
|

Testing the consistency of dust laws in SN Ia host galaxies: A BayeSN Examination of Foundation DR1

Abstract: We apply BayeSN, our new hierarchical Bayesian model for the SEDs of Type Ia supernovae (SNe Ia), to analyse the griz light curves of 157 nearby SNe Ia (0.015 < z < 0.08) from the public Foundation DR1 dataset. We train a new version of BayeSN, continuous from 0.35–0.95 μm, which we use to model the properties of SNe Ia in the rest-frame z-band, study the properties of dust in their host galaxies, and construct a Hubble diagram of SN Ia distances determined from full griz light curves. Our griz H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
37
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 121 publications
10
37
2
Order By: Relevance
“…We note that this is comparable to the light-curve scatter from other low-z samples in the literature, when analysed with the SALT2 model (see, e.g. Thorp et al 2021 ) as well as low-z sample of SNe Ia used in cosmological studies (e.g. Scolnic et al 2018 ).…”
Section: Hubble Residualssupporting
confidence: 81%
“…We note that this is comparable to the light-curve scatter from other low-z samples in the literature, when analysed with the SALT2 model (see, e.g. Thorp et al 2021 ) as well as low-z sample of SNe Ia used in cosmological studies (e.g. Scolnic et al 2018 ).…”
Section: Hubble Residualssupporting
confidence: 81%
“…Smith et al ( 2020 ) found a difference of up to 0.04 mag in the average intrinsic magnitude of the two groups, and application MNRAS 514, 139-163 (2022) of the Tripp relation to the two groups separately may further reduce the residual dispersion in SNIa absolute magnitudes. (See also Thorp et al ( 2021 ) for a similar result obtained using a Bayesian hierarchical approach.) Ho we ver, have recently cast doubt on the robustness of this mass-step correction, which they ascribed instead to incorrect dust modelling.…”
Section: Bayesian Hierarchical Modelsupporting
confidence: 54%
“…However, there are now two well-vetted light-curve models extending to the NIR: the SNooPy model (Burns et al 2011(Burns et al , 2014 and the BayeSN model (Thorp et al 2021;Mandel et al 2022).…”
Section: Nir Light-curve Modelsmentioning
confidence: 99%
“…Brout et al 2022). In the optical bands, where most SN Ia data have been obtained, substantial deviations from the behavior of a standard candle are reduced by correcting for the observed relations between light-curve shape and luminosity (Pskovskii 1977;Phillips 1993;Hamuy et al 1996;Riess et al 1996;Guy et al 2007;Jha et al 2007;Conley et al 2008;Mandel et al 2011;Burns et al 2014), reddening by dust (Riess et al 1996;Phillips et al 1999;Burns et al 2014;Thorp et al 2021;Mandel et al 2022), and the intrinsically redder color of less luminous SNe Ia (Tripp 1998;Mandel et al 2017).…”
Section: Introductionmentioning
confidence: 99%